(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Diagnostic validity of different tests for the detection of spontaneous subarachnoid haemorrhage is an important issue. Objectives: The purpose of the present study was to validate 3D-Computed tomographic angiography in spontaneous subarachnoid haemorrhage. Methodology: This cross-sectional study was carried out in the Department of Neurosurgery and Cath Lab of DMCH in collaboration with private diagnostic centre from September 2013 to February 2015 for a period of six (06) months. Adult patients diagnosed as a case of spontaneous SAH based on clinical features and confirmed by plain CT evidence of subarachnoid blood were included as study population. Patients having current history of trauma, poor clinical grade and agitated patient, patient with renal insufficiency, known allergy to iodinated contrast agent and patients who were not willing participate in the study were excluded from this study. Then both CT angiography and DSA were performed to detect cause of bleeding and to make a treatment planning. In this study DSA was considered as reference standard for evaluation of CTA. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of CTA were calculated per patient basis and per aneurysmal basis. Result: A total number of 37 patients presented with spontaneous subarachnoid haemorrhage were recruited for this study. The mean age of patients was 58.53±7.54 years. Sensitivity and specificity in depicting intracranial aneurysms were, 93.75% and 100% respectively on a per-patient basis. Positive predictive value and negative predictive value of CTA are 100% and 71.43% respectively. CTA had shown 94.59% accuracy in detection of intracranial aneurysm. Sensitivity and specificity in depicting intracranial aneurysms were 94.74% and 100% respectively on a per-aneurysm basis. Positive predictive value and negative predictive value of CTA are 100% and 71.43% respectively. CTA had shown 95.35% accuracy in detection of intracranial aneurysm. Conclusion: In conclusion CTA has high detection capacity of aneurysm among spontaneous subarachnoid haemorrhage patients. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 47-52